Social, economic, and gender dimensions in Islamic economics: A cross-country comparative study for advancing Maqāṣid al-Sharī‘ah and the SDGs - Tri Astuti; Lapipi; Muhammad Yani Balaka; Marjani; Dwi Kartika Prananingrum; Hasddin; Irham Natsir Kelana (Faculty of Social and Political Science, Universitas Airlangga, 2026)
This study evaluates the role of gender empowerment measures in improving the performance, sustainability, and social acceptance of Islamic Financial Institutions (IFIs) across different cultural and regulatory environments. This study aims to understand the impact of gender diversification tactics on IFI profitability, identify the best Islamic financial products aimed at increasing women’s involvement, identify cross-country differences in the performance of these measures, understand the challenges and opportunities for promoting gender equality in Islamic finance. This study uses CNCCA to analyze IFIs across countries. A total of 89 secondary sources, including institutional reports and peer-reviewed studies, were used. The study finds that inclusive models such as Cash Waqf-Musharakah, Qardhul Ḥasan for Women, Women-Centered Crowdfunding, and Women in Leadership have a positive impact on profitability, institutional legitimacy, and social stability. The use of technology and flexible Sharia contracts also improves operational efficiency, risk management, and access to productive financing. Adaptations are context-specific: Southeast Asia leads in digital micro-inclusion, the Middle East emphasizes regulatory support, and sub-Saharan Africa benefits from a hybrid zakat-wakf model. In conclusion, theoretically linking Islamic economics to gender empowerment and regional development, while practically offering evidence based strategies for policymakers and Islamic financial institutions to support SDGs, is important.